An Analysis of Thematic Progression in High School Students’ Exposition Texts - Asri Nur Rakhman (Universitas Pendidikan Indonesia (UPI), 2013)
This study aims to investigate how high school students organize their ideas in their Exposition texts, and to what extent their Exposition texts are consistent with argumentative language features in terms of Thematic Progression, based on the framework of Systemic Functional Linguistics (e.g. Danes, 1974; Eggins, 2004). The data were nine high school students’ Exposition texts from low, middle, and high level of achievement. The result shows that the students organize their ideas in three ways of Thematic Progression, including the Zig-zag Pattern or Simple Linear Theme Progression (SLP), the Re-iteration Pattern or Constant Theme Progression (CTP), and the Multiple Theme Pattern or Derived Theme Progression (DTP). In terms of Thematic Progression consistency, some texts from middle and high achievers are consistent with the argumentative language features, since they employed SLP than CTP and used DTP. Some students still need guidance to create good pieces of writing.Keywords: Thematic Progression, Exposition text, Senior High School